Morphometric Characterization Study of Apis cerana Worker Bees in North Lombok Regency - Erwan, Erwan; Muhsinin, Muhammad; Herlambang, Dany Alfian (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Honeybees (Apis cerana) are one of the indigenous honeybee species of Asia. They serve a crucial function in ecosystems, mostly as pollinators. This study investigates the morphometric characteristics of Apis cerana worker bees in North Lombok Regency, focusing on two beekeeping groups: Harapan Keluarga and Tunas Muda, located in Salut village, Kayangan District North Lombok Regency. Morphometric analysis was conducted on 40 colonies, with measurements taken from eight key body traits: body length, abdomen length, femur length, tibia length, metatarsus length, forewing length, hindwing length, and body weight. Results revealed significant differences between the two locations. Tunas Muda bees exhibited larger morphometric traits with lower coefficient variations, indicating higher population uniformity. Correlation and regression analyses showed that body length, forewing length, and abdomen length strongly influence body weight, with body length having the highest correlation (r = 0.85) and determination coefficient (R2 = 0.722). The study highlights the impact of environmental factors, management practices, and nutritional conditions on bee morphology. These findings provide critical insights for enhancing beekeeping practices, supporting honeybee conservation efforts, and exploring genetic and physiological adaptations in Apis cerana. This research underscores the importance of integrating morphometric analysis into sustainable apiculture and biodiversity conservation strategies in North Lombok.